School daily as a principale of research in education - Maia, Graziela Zambão Abdian [UNESP] (Universidade Estadual de Maringa, 2020)
The history of knowledge in Education Administration in Brazil is based on two paradigms: business management and school specificity or democratic management, which is the overcoming of the previous one. After the 1990s, research in Education Policy and Management privileges the school as a research entity and analyzes it based on the theory of democratic management. In this article, the objective is to explore theoretical-methodological references used by researchers who have the school as a research institution, analyze their weaknesses and defend the position that everyday school life can be understood as a research principle. If so, it also proposes the discussion of three major challenges to researchers in the field: the directions of critical theory and criticism itself; the theory and practice relations; and the meanings of politics and management. The first challenge is to conceive of criticism as an attitude of virtue, of voluntary indulgence, and as a possibility of disassociating ourselves from the ways of producing truths in the relation between subject, power and truth. This attitude of virtue presupposes as a second challenge the attempt to conceive of new relations of theory and practice that escape normativism and the prescriptive model. As a third challenge, it is pointed out that previous reflections make it possible to question the practical meanings that circulate and legitimize a way of thinking in the area, specifically, politics and management.
Escuela diaria como principio de investigación en educación
O cotidiano escolar como princípio das pesquisas em educação
Keywords: administration of education; critical theory; political; politics